Audyt wewnętrzny w organizacjach gospodarczych - perspektywy rozwoju - Kluska, Katarzyna (The Internal Audit in Economic Entites - The Prospects of Development, 2006)
The main aim of this paper is to show how important for a company is internal audit. Internal audit is an independent, objective assurance and consulting activity designed to add value and improve an organization's operations. Internal auditors should have an impartial, unbiased attitude and avoid conflicts of interest. Internal auditors should possess the knowledge, skills and other competencies needed to perform their individual responsibilities. They should also enhance their competencies through continuing professional development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 158-165